Live-storage of wild mature cod (Gadus morhua L.) without feed supply. Effects on biological and quality properties - Ageeva, Tatiana N. (UiT The Arctic University of Norway, 2018)
Paper II of this thesis is not available in Munin. Paper II: Ageeva, T. N., Olsen, R. L., Joensen, S., & Esaiassen, M. (2018). Effects of Long-Term Feed Deprivation on the Development of Rigor Mortis and Aspects of Muscle Quality in Live-Stored Mature Atlantic Cod (Gadus Morhua L.). Available in Journal of Aquatic Food Product Technology, 27(4), 477-485. The overall aim of this work was to obtain better understanding of how live-storage without feeding affects wild mature Atlantic cod (Gadus morhua L.) and quality of products obtained from such cod. Atlantic cod were live-stored without feeding for 82 days. First, gender-specific weight changes in both whole and gutted fish, as well as certain organs were studied (Paper I). Next, the effects of feed deprivation on development of rigor mortis, as well as aspects of muscle properties were investigated (Paper II). Finally, changes in quality of fillet products, both due to feed deprivation and different times of processing were studied (Paper III). The results showed that the cod were spawning during the first 54 days in captivity, leading to a great loss of total weight. The main changes in gutted weight were detected in the post-spawning period. Females were affected more severely by feed deprivation than males. This sexual dimorphism became more evident towards the termination of the trial, when females had lost more total and gutted weights, liver mass and had a significantly lower muscle protein concentration than males. Feed deprivation for 23 days reduced pre rigor time from 29 to 17 h while further feed deprivation did not reduced this time significantly. If the fish are slaughtered under non-stressful conditions, the pre rigor time in feed-deprived cod can still be long enough to process the fish prior to the onset of rigor mortis. Feed deprivation resulted in just a small reduction in contraction of pre rigor made products. The tail products, especially made pre rigor, contracted more and had higher drip loss than loins and whole fillets. The ...